Evidence of obesity-induced inflammatory changes in client-owned cats - Steffi L. Araujo; Patricia L. Martins; Thyago H. de Souza Pereira; Tiago L. Sampaio; Ramon R. Paula Pessoa Bezerra de Menezes; Mac D. Rodrigues da Costa; Alice M. Costa Martins; Isaac Neto Goes da Silva; Glayciane Bezerra de Morais; Janaina Serra Azul Monteiro Evangelista (Veterinary World, 2024)
Background and Aim: Insulin resistance and type 2 diabetes mellitus are common health issues in obese (OB) cats. In humans, obesity leads to alterations in adipokine and proinflammatory cytokine secretion, causing persistent inflammation. The inflammatory impact of obesity in cats remains unproven. This study investigated associations between obesity and inflammatory and metabolic changes in three groups of client-owned Brazilian domestic shorthair cats: naturally lean, overweight (OW), and OB.